Humanising Digital Language Education 5.0 through a Freirean Lens - Kildė, Laura (Acta Paedagogica Vilnensia, 2025)
The current paper employs the ontological and epistemological principles of critical pedagogy, namely Freire’s approach, to contemporary foreign language education by aligning his key tenets to the requirements set for both teachers and students in AI Guidelines. Document analysis highlights opportunities and challenges that, in a Freirean sense, are required to defy the banking concept of education by yielding conscientization and praxis in order to diminish student-teacher dichotomy and reach dialogue. The present conceptual analysis reinvents Freirean insights to provide implications for a humanised approach towards GenAI employment for language teacher education and their continuous education renewal.
Keywords: foreign language education; AI guidelines; GenAI; Freire; critical pedagogy